On Gender Difference and Cultural Diversity of the Balkans: Interview with Suzana Milevska: За родовата разлика и културната разноликост на Балканот: Интерву со Сузана Милевска - Trajanoski, Žarko; Milevska, Suzana (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Žarko Trajanoski and Suzana Milevska | Жарко Трајаноски и Сузана Милевска Title (English): On Gender Difference and Cultural Diversity of the Balkans: Interview with Suzana Milevska Title (Macedonian): За родовата разлика и културната разноликост на Балканот: Интерву со Сузана Милевска Translated by (English to Macedonian): Žarko Trajanoski | Жарко Трајаноски Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No. 2 (Summer 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 159-171 Page Count: 12 Citation (English): Žarko Trajanoski and Suzana Milevska, “On Gender Difference and Cultural Diversity of the Balkans: Interview with Suzana Milevska,” Identities: Journal for Politics, Gender and Culture, Vol. 5, No. 2 (Summer 2006): 159-171. Citation (Macedonian): Жарко Трајаноски и Сузана Милевска, „За родовата разлика и културната разноликост на Балканот: Интерву со Сузана Милевска“, превод од англиски Жарко Трајаноски, Идентитети: списание за политика, род и култура, т. 5, бр. 2 (лето 2006): 159-171.